Proceedings of the Ninth Annual Meeting of the Agro-Climatic Regional Planning Project - Planning Commission (Planning Commission, 1998)
The second day was divided into four technical sessions, all chaired by Prof. SR Hashim. The first two sessions of the day were on the "Role of ZPTs in Future ACRP Research" and "Operationalization of the ACRP Approach". Technical Session 11 on "Role of ZPTs in Future ACRP Research" started with Dr. SN Joshi giving a brief overview on future research agenda of ZPT. This was followed by presentations by Prof. KS Chauhan. Vice Chancellor, Rajendra Agricultural University Pusa (Bihar), Prof. AG Sawant Vice Chancellor. Konkan Krishi Vidyapceth Dapoli (Maharashtra), and Prof. HP Khound Planning and Evaluation Officer, Assam Agricultural University, Jorhat (Assam).
Agro-Climatic Regional Planning Unit (Planning Commission)
Government of India Planning Commission
Keywords: Inaugural Session; Research and Dissemination of ACRP; Role of ZPTs in Future ACRP Research; Operationalisation of ACRP- Experimental Projects; Internalisation of ACRP in Planning Framework- Institutionalization Exercise; Future of ACRP In the Ninth Plan; Non-spatial Database; Fertilizers; Plant Protection; Agromet Elements; Agricultural Implements